Memory and affective changes during the antepartum: A narrative review and integrative hypothesis. Issue 1 (2nd January 2019) - Ouellette, Sarah J.; Hampson, Elizabeth
ABSTRACT: Introduction and objectives : Many women report diminished memory function during the second or third trimesters of pregnancy, but objective neuropsychological tests often fail to show any decrement in performance. The present paper systematically reviews published studies that have investigated this phenomenon over the past 25 years and considers newer studies showing that affective changes occur during gestation in a subset of pregnant women. Method : A systematic search was conducted to identify articles relevant to pregnancy and memory function. Articles published since 1990 that included a nonpregnant comparison group were retained for review. Results : A literature review of studies using objective memory testing suggests that a mild antepartum decline in explicit verbal recall occurs in some women. There is little empirical support for objective changes in semantic or implicit memory during pregnancy. Findings for working memory are mixed, with evidence supporting both decrements and enhancements. Inconsistencies in the literature potentially reflect a moderating influence of pregnancy-linked depressive affect on cognitive performance, not simply domain specificity, as previously suggested. Conclusions : Diminished memory function may occur in a specific subset of pregnant women who display depressive symptoms associated with pregnancy.